An Investigation of Electrocatalytic CO2 Reduction Using a Manganese Tricarbonyl Biquinoline Complex - McKinnon, Meaghan; Belkina, Veronika; Ngo, Ken T.; Ertem, Mehmed Z.; Grills, David C.; Rochford, Jonathan (Frontiers in Chemistry, 2019)
The subject of this study, [fac-Mn(bqn)(CO)3(CH3CN)]+ (bqn = 2,2’-biquinoline), is of particular interest as the bqn ligand exhibits both steric and electronic influence over the fundamental redox properties of the complex and, consequently, its related catalytic properties with respect to the activation of CO2. While not a particularly efficient catalyst for CO2 to CO conversion, in-situ generation and activity measurements of the [fac-Mn(bqn)(CO)3]– active catalyst allows for a better understanding of ligand design at the Mn center. By making direct comparisons to the related 2,2’-bipyridyl (bpy), 1,10-phenanthroline (phen), and 2,9-dimethyl-1,10-phenanthroline (dmphen) ligands via a combination of voltammetry, infrared spectroelectrochemistry, controlled potential electrolysis and computational analysis, the role of steric vs electronic influences on the nucleophilicity of Mn-based CO2 reduction electrocatalysts is discussed.